Ruta Cultural de las parroquias Taquil, Chantaco y Chuquiribamba, Cantón Loja, Provincia de Loja - VEINTIMILLA LOAIZA, DANNY MICHAEL (2018)
Cultural tourism is understood as a form of tourism that aims to promote knowledge of culture in all its expressions, as well as being understood as a category that complements other participatory and creative forms of culture, including those generated by the own trip, and relations with the destination communities. Cultural tourism is configured as a concept in the process of construction, where the supply of resources and products based on monumental and material heritage are integrated, and also where the demand and its motivations are incorporated, generating an increasingly broad and integrating cultural tourism. The province of Loja and especially the canton of the same name, stand out for the enormous cultural wealth they possess, which makes this place, the ideal for the implementation of cultural tourism products that are currently scarce in this part of the country. For this reason it is proposed in this research the development of a new product, whose main objective is the creation of a cultural tourist route in the parishes of Taquil, Chantaco and Chuquiribamba, of Loja, in the province of Loja; where three specific objectives are also complemented to complement the proposal. The first objective, to carry out a tourist diagnosis of the Taquil, Chantaco and Chuquiribamba parishes, Loja canton, province of Loja, has the purpose of establishing a basic knowledge of each one of the analyzed parishes. For this, the analytical method is used to disaggregate the main characteristics of these sites. Relying on different methodologies, such as the local tourism diagnosis of Carla Ricaurte, the SWOT matrix to determine the internal and external factors of the area; the MARPP technique for analyzing rural sectors and also from direct observation techniques and interviews with key actors; This research objective was developed. For the development of the second objective, to elaborate a proposal of cultural tourist route of the parishes of Taquil, Chantaco and Chuquiribamba, canton Loja, province of Loja; the georeferencing technique was applied to position the points that comprise the route, which were selected with the elaboration of the tourist inventory cards of the Ministry of Tourism of Ecuador (MINTUR). The route was elaborated from the data obtained from the diagnosis and with it the proposal that takes by name was proposed: Touristic Route – Cultural Roads; and the slogan: "Experience the culture". The proposed route also includes an itinerary with its respective script; application of signage and promotional strategies and dissemination of the tourist product. Finally, the third objective, to socialize the results of the investigative work with the actors immersed in the research project; It was carried out by holding a participatory workshop with authorities and part of the population of the three parishes involved in the project. Here a debate was developed to solve the doubts of the assistants, as well as so that they can make some 5 As a final conclusion it is highlighted that the proposal of the cultural touristic route of the Loja countryside, allows to position the rural parishes in the provincial tourist map, as places of a cultural richness that deserves to be appreciated and recognized at local and national level. In the same way, the proposal allows parishioners to generate greater tourist awareness and know the intrinsic value they possess. As a recommendation to the authorities, it is proposed to provide more support to the ideas and undertakings of its inhabitants, as they often see their ideas stalled by the lack of investment and support from their authorities.